Tax loss offset restrictions and biased perception of risky investments - Annika Mehrmann; Caren Sureth-Sloane (Arbeitskreis Quantitative Steuerlehre (arqus), 2017)
We investigate how tax loss offset restrictions affect an investor's evaluation of risky investments under bounded rationality. We analytically identify behavioral tax effects for different levels of loss offset restrictions, tax rate and prospect theoretical biases (loss aversion, probability weighting and reference dependence) and find tax loss offset restrictions significantly bias investor perception, even more heavily than the tax rate. If loss offset restrictions are rather generous, investors are very loss averse or assign a huge weight to loss probabilities, taxation is likely to increase the preference value of risky investments (behavioral tax paradox). Surprisingly, the identified significant perception biases of tax loss offset restrictions occur under both high and low tax rates and thus are relatively insensitive to tax rate changes. Finally, we identify huge differences in behavioral tax effects across countries indicating that tax loss offset restrictions crucially determine the perceived tax quality of a country for risky investments. Our analysis is relevant for policy makers discussing future tax reforms as well as for investors assessing risky investment opportunities.
Keywords: D81; D91; H21; H25; 330; asymmetric taxation; investment decisions; loss offset restrictions; perception bias; risktaking; tax effects; tax losses; prospect theory; behavioral taxation